Secure Data Acquisition Integration Framework for Key Management and Multilayer Security (International Journal of Scientific Research in Science and Technology, 2024)
In the era of digital transformation, the need for robust data security and efficient key management has never been more critical. An organization handling sensitive information across various domains, such as finance, healthcare, and government, requires a comprehensive solution to safeguard their data assets. This abstract introduces a cutting-edge framework designed to address these challenges – the Secured Data Acquisition Integrating Framework (SDAIF) for Key Management and Multilayer Security. SDAIF represents a holistic approach to data security, encompassing data acquisition, encryption, key management, and multilayer security protocols. The framework’s primary objective is to provide a unified and extensible system for organizations to protect their data from unauthorized access, tampering, and data breaches. The Secured Data Acquisition Integrating Framework (SDAIF) for Key Management and Multilayer Security represents a comprehensive solution to the increasingly complex data security challenges faced by organizations today. By adopting SDAIF, organizations can strengthen their data protection measures, reduce the risk of data breaches, and ensure the confidentiality, integrity, and availability of their critical data assets.